High-resolution reconstruction of the beating zebrafish heart - Mickoleit, Michaela; Schmid, Benjamin; Weber, Michael; Fahrbach, Florian O.; Hombach, Sonja; Reischauer, Sven; Huisken, Jan (Nature Methods, 2014)
The heart's continuous motion makes it difficult to capture high-resolution images of this organ in vivo. We developed tools based on high-speed selective plane illumination microscopy (SPIMIM), offering pristine views into the beating zebrafish heart. We captured three-dimensional cardiac dynamics with postacquisition synchronization of multiview movie stacks, obtained static high-resolution reconstructions by briefly stopping the heart with optogenetics and resolved nonperiodic phenomena by high-speed volume scanning with a liquid lens.
Created from Fastlane, Scopus look-up